LOW COST WIRELESS ECG PATCH USING ESP32 - Budi Sugandi; Muhammad Haikal Satria; Hamdani Arif; Nelmiawati Nelmiawati; Indra Hardian Mulyadi (JURNAL INTEGRASI, 2020)
Wearable-and-wireless Electrocardiograph (ECG) has been widely used for long term monitoring due to practical reasons. Besides its high Signal to Noise Ratio (SNR), one of patch benefits is its flexibility for users to place the electrodes. However, most of existing commercial wireless ECG patches displays Heart Rate Variability (HRV) only, without ability to provide or record the ECG waveform. Some of them employ two electrodes only: Right Arm (RA) and Left Arm (LA), without additional electrode called Right Arm Drive (RLD). In addition, It is beneficial to provide more than one wireless technology option for ECG patch. We propose a low cost wireless ECG patch that has ability to provide ECG waveform (Lead I) and calculate HRV automatically. Besides RA and LA, it utilized RLD electrode to increase Common Mode Rejection Ratio (CMRR). For data processing, we employed ESP32, a low-power 32-bit microcontroller equipped with Bluetooth Classic (BT), Bluetooth Low Energy (BLE), and Wifi in a compact module. The test results showed that the proposed ECG patch resulted in more accurate HRV calculation as well as 2,7 times faster transition time compared to a commercial product.